“Assistance is from you, if you do good deeds” (Devoted to the creative work of Habibullah Kerem (1848 – 1913)) - Ismail Kerimov (Крымское историческое обозрение)
The article deals with the work of one of little-known authors of the Crimean Tatar literature of the late 19th century and early 20th Habibullah Kerem. Based on manuscripts, kept today in the archives of St.Petersburg, as well as rare sources related to the events of the time, the article describes a brief biography in comparative terms analyzing the poetic legacy of the author.